Pengaruh Interval Pemotongan dan Invasi Gulma Chromolaena odorata terhadap Produksi dan Kualitas Rumput Brachiaria humidicola - . Mansyur; H Djuned; T Dhalika; S Hardjosoewignyo; L Abdullah (Media Peternakan, 2005)
An excellent animal performance has to be supported by feed availability. Quality and quantity of forages are important factors. The existence of weeds significantly decreases rate of production and quality of herbage. Physically weed control by defoliation could be expected to sustain quality and production of herbage, and able to control weeds expansion. The aims of the study were to find the effect of interval defoliation of B. humidicola that was invaded by C. odorata and its effect on production, crude protein, phosphor, calcium contents of B. humidicola herbage, production and population dynamic of C. odorata. The treatments were nine different planting methods and different defoliation intervals, namely: B. humidicola was defoliated every 30 days without C. odorata (P1); B. humidicola was defoliated every 60 days without C. odorata (P2); B. humidicola was defoliated every 90 days without C. odorata (P3); B. humidicola were defoliated every 30 days, C. odorata were not defoliated (P4); B. humidicola were defoliated every 60 days, C. odorata were not defoliated (P5); B. humidicola were defoliated every 30 days, C. odorata were not defoliated (P6); B. humidicola and C. odorata were defoliated every 30 days (P7); B. humidicola and C. odorata, were defoliated every 60 days (P8); B. humidicola and C. odorata were defoliated every 90 days (P9). Two experiment designs namely Completely Randomized Block Design and Split Plot Design in Time were used in the field experiments. The result of the experiments showed that dry matter production of B. humidicola which were defoliated every 90 days were not significantly different than those defoliated every 60 days, but it was significantly higher than those defoliated every 30 days. Crude protein, phosphor, and calcium content of herbage which were defoliated every 30 days were significantly higher than those defoliated every 60 days and 90 days. Present and defoliation of C. odorata did not affect the herbage production, and phosphor content, but it decreased crude protein and calcium content of B. humidicola herbage. Keywords: production, quality, herbage, defoliation interval